2020
DOI: 10.1007/s11739-020-02586-8
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in SARS-CoV-2 hospitalised patients: a case-series with a focus on drug–drug interactions

Abstract: Due to the need of early and emergency effective treatments for COVID-19, less attention may have been paid to their safety during the global emergency. In addition, characteristics of drug–drug interaction (DDI)-related adverse drug reactions (ADRs) in COVID-19 patients have not yet been studied in depth. The aim of the present case-series study is to describe clinical and pharmacological characteristics of SARS-CoV-2 hospitalised patients, focusing on ADRs, particularly those related to DDIs. We evaluated al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
1
30
1
1
Order By: Relevance
“…Nevertheless, for a better general understanding and a wide comparability between settings, Naranjo scale still plays a role, although, as stated in several pharmacovigilance studies, the scale presents numerous well-known application limits [5]. Finally, as reported in Table 2 [2], none of adverse drug reactions described in our study were assessed as "certainly" associated with the suspected drugs.…”
mentioning
confidence: 67%
“…Nevertheless, for a better general understanding and a wide comparability between settings, Naranjo scale still plays a role, although, as stated in several pharmacovigilance studies, the scale presents numerous well-known application limits [5]. Finally, as reported in Table 2 [2], none of adverse drug reactions described in our study were assessed as "certainly" associated with the suspected drugs.…”
mentioning
confidence: 67%
“…A study done by Sun et al reported hepatobiliary and gastrointestinal symptoms as the main manifestations of ADRs [9]. However, in the case series by Crescioli et al, 2020, it was concluded that the ADRs related to cardiovascular, psychiatric and gastrointestinal disorders were the most frequent [15].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published papers on drug interactions in COVID patients consist of presenting potential interactions to which patients have been exposed after reviewing medical records [30][31][32] (no specific outcome). We have found 2 papers [33,34] with individual descriptions of the clinical cases presented in eTable 31 (use suppInfo).…”
Section: Literature Researchmentioning
confidence: 99%